Elite capture or capture elites? Lessons from the 'counter-elite' and 'co-opt-elite' approaches in Bangladesh and Ghana - Sam Wong (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
Community-based development has been criticized for its inadequate understanding of power relationships at the local level, which thus leaves room for elite capture. This paper compares and contrasts two case studies, both of which take power seriously in their institutional designs. The solar home system in Bangladesh, represents the 'counter-elite' approach and explicitly excludes local elites from the decision-making process. The trans-boundary water governance project in Ghana, in contrast, adopts the 'co-opt-elite' approach and deliberately absorbs local elites into the water committee. This paper suggests that, while the - counter-elite - approach is not necessarily effective in challenging elite domination, because of the structural asset dependence of poor people on the elites, the 'co-opt-elite' approach risks legitimizing the authority of the elites and worsening poverty by implementing 'anti-poor' policies. This paper concludes that the success of dealing with elite capture lies in the flexible use of the 'counter-elite' and 'co-opt-elite' approaches together with the need to secure alternative livelihoods and to achieve empowerment with the poor.
Keywords: Z1; O3; 330; elite capture; power; poverty; community development; water management; solar lighting